2015
DOI: 10.1103/physreva.91.012120
|View full text |Cite
|
Sign up to set email alerts
|

Experimental test of environment-assisted invariance

Abstract: Envariance, or environment-assisted invariance, is a recently identified symmetry for maximally entangled states in quantum theory with important ramifications for quantum measurement, specifically for understanding Born's rule. We benchmark the degree to which nature respects this symmetry by using entangled photon pairs. Our results show quantum states can be (99.66 ± 0.04)% envariant as measured using the quantum fidelity, and (99.963 ± 0.005)% as measured using a modified Bhattacharya coefficient, as compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 18 publications
1
17
1
Order By: Relevance
“…In turn, we found that the ñ L | polarization state was accompanied by the -ñ 1 | and + ñ 1 | OAM states with respective frequencies of 98.4±0.3% and 1.6±0.3%, showing close correspondence with Premise III. We close with a brief comment to place this work in context, particularly with respect to the results presented in the investigation [9]. While reference [9] and the present study both reported an experimental investigation of envariance, the two projects differed considerably in scope and aim.…”
Section: Experiments and Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…In turn, we found that the ñ L | polarization state was accompanied by the -ñ 1 | and + ñ 1 | OAM states with respective frequencies of 98.4±0.3% and 1.6±0.3%, showing close correspondence with Premise III. We close with a brief comment to place this work in context, particularly with respect to the results presented in the investigation [9]. While reference [9] and the present study both reported an experimental investigation of envariance, the two projects differed considerably in scope and aim.…”
Section: Experiments and Resultsmentioning
confidence: 74%
“…With these preliminaries in place, we now begin by briefly reviewing the derivation of the Born rule, which motivates this investigation, bearing in mind that the simple scenario discussed here is readily generalized to the case of arbitrary quantum states (see: appendix A). In this approach, one considers a bipartite quantum state S y ñ E | , formed from an interaction between a system S and its environment 9 û and E û must be envariant, and cannot be attributed to either the system or the environment alone. To make the case for the BPR, we adopt the following notational convention: for an observer having access only to the Hilbert space to which belongs a state ñ…”
Section: Theorymentioning
confidence: 99%
“…1 and Fig. 2, and there are now several experiments [28][29][30][31] that test some of the tenets of the derivation we are about to present.…”
Section: Probabilities From Entanglementmentioning
confidence: 89%
“…Thus, Ref. [28] use Hong-Ou-Mandel effect [36] to verify envariance of entangled and spatially separated photons (e.g., they carry out in the § When the probabilities are incommensurate, one uses sequences of states with commensurate probabilities (deduced from the Schmidt coefficients as above) that converge, from above and below, on these incommensurate probabilities: Such sequences "bracket" the incommensurate probabilities. We assume that probabilities are continuous functions of quantum states.…”
Section: Discussion Of Envariant Derivation Of Born's Rulementioning
confidence: 99%
“…2. Degenerate photon pairs are prepared using type-II spontaneous parametric down-conversion in a Sagnac interferometer [40]. We pump a 10 mm long periodicallypoled KTP crystal (PPKTP) with a continuous wave diode laser (404.8 nm) to produce correlated photon pairs centered at λ SP = 810.8 nm with a spectral bandwidth of 0.4 nm.…”
mentioning
confidence: 99%